The Impact Of Total Quality Management Practices On Employee's Work Related Attitude - Karia, Noorliza (1999)
This study examined the impact of TQM practices have on employee's work related attitude. TQM practices have been adopted as new management practices in improving organization commitment to quality of product or service. TQM practices create a culture that encourages employee involvement, motivation, satisfaction and commitment. In this study, the indicators of work related attitudes are job involvement, job satisfaction, career satisfaction and organizational commitment. This study gathers the information about the impact of TQM practices on 104 employees working in 5 organizations in Penang that practice TQM.